2016
DOI: 10.1039/c6ra00901h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a covalent edge-functionalized lipoic acid–MoS2conjugate

Abstract: Here, we developed a one-step method for covalent edge functionalization of semiconducting MoS2with lipoic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 57 publications
(86 reference statements)
3
33
0
Order By: Relevance
“…[64] Similarly, other thiol-terminated ligands such as mercaptopropionic acid, 1-thioglycerol and L-cysteine were also chemically conjugated on the edges of MoS 2 and WS 2 nanosheets during their exfoliation process. [66] Recently, Lee's group reported the covalent binding of sulfur-containing groups on the surface sulfur vacancies of micromechanically exfoliated MoS 2 (Figure 4a), as indicated by the Raman spectral change of the surface-modified MoS 2 films (Figure 4b). [66] Recently, Lee's group reported the covalent binding of sulfur-containing groups on the surface sulfur vacancies of micromechanically exfoliated MoS 2 (Figure 4a), as indicated by the Raman spectral change of the surface-modified MoS 2 films (Figure 4b).…”
Section: Surface Modification With Organic Moleculesmentioning
confidence: 97%
“…[64] Similarly, other thiol-terminated ligands such as mercaptopropionic acid, 1-thioglycerol and L-cysteine were also chemically conjugated on the edges of MoS 2 and WS 2 nanosheets during their exfoliation process. [66] Recently, Lee's group reported the covalent binding of sulfur-containing groups on the surface sulfur vacancies of micromechanically exfoliated MoS 2 (Figure 4a), as indicated by the Raman spectral change of the surface-modified MoS 2 films (Figure 4b). [66] Recently, Lee's group reported the covalent binding of sulfur-containing groups on the surface sulfur vacancies of micromechanically exfoliated MoS 2 (Figure 4a), as indicated by the Raman spectral change of the surface-modified MoS 2 films (Figure 4b).…”
Section: Surface Modification With Organic Moleculesmentioning
confidence: 97%
“…Continued irradiation is expected to divide the 2D sheets into multiple 2D nanoparticles, as illustrated in the upper portion of Figure 1b. [19] After laser treatment, solutions were centrifuged for 10 min, and then the upper portion of the solution was extracted and drop cast onto a supporting substrate for characterization. While basal plane functionalization is also possible, the mechanism proposed here is consistent with preferential edge functionalization.…”
mentioning
confidence: 99%
“…While basal plane functionalization is also possible, the mechanism proposed here is consistent with preferential edge functionalization. [19] After laser treatment, solutions were centrifuged for 10 min, and then the upper portion of the solution was extracted and drop cast onto a supporting substrate for characterization.…”
mentioning
confidence: 99%
“…After functionalization, MoS 2 NSs exhibited remarkably enhanced biocompatibility and colloidal stability in physiological conditions. Jeong et al functionalized 2H‐MoS 2 with LA via a simple sonochemical aqueous dispersion procedure . High resolution TEM (HRTEM) images showed that LA molecules attached to the edges of MoS 2 NSs and generated LA‐MoS 2 conjugates with intact crystalline basal planes.…”
Section: Surface Functionalization Of 2d Tmdc Nssmentioning
confidence: 99%
“…Jeong et al functionalized 2H-MoS 2 with LA via a simple sonochemical aqueous dispersion procedure. [113] High resolution TEM (HRTEM) images showed that LA molecules attached to the edges of MoS 2 NSs and generated LA-MoS 2 conjugates with intact crystalline basal planes. X-ray diffraction (XRD) patterns showed that the LA-MoS 2 conjugates formed randomly stacked trigonal prismatic 1H structure, suggesting that the functionalization did not alter the innate phase polytype of MoS 2 NSs.…”
Section: Coordinate Functionalizationmentioning
confidence: 99%